(untitled) (Journal of Nepal Geological Society, 1982)
High grade mineralisation of zinc and lead sulphides occur near the Main Central Thrust (MCT) Zone of the Himalaya in the lower regions of Ganesh Himal Range in Nepal. The host rock is crystalline dolomitic limestone showing tremendous flow in a highly folded sequence of garnetiferous mica-schist, quartzites, calcareous schists, and bands of hornblende gneiss. The stratigraphic control and the simple nature of mineralisations suggest a syn-sedimentary genesis.